Pemulihan Post Traumatic Stress Disorder Q.S Al-Baqarah : 155 (Studi Komparatif: Tafsir Al-Misbah, Tafsir Al-Munir, Tafsir Al- Azhar) - Siregar, Annisa Aurora (TSAQOFAH, 2023)
Post Traumatic Stress Disorder Recovery in Al-Qur'an QS. Al-Baqarah: 155 (Comparative Studies: Tafsir Al-Misbah, Tafsir Al-Munir, Tafsir Al-Azhar), which contains stress recovery after a person experiences trauma. Religion can affect stress patterns, so those who have a religious life tend to only experience anxiety, while those who do not have a religious life tend to experience severe stress and even depression. In PTSD recovery, researchers have studied several Qur'anic verses that can be used as a PTSD recovery process, such as QS. Al-Baqarah verse 45 about prayer, QS. Al-Baqarah verse 155 about patience, and QS. Ar-Rad verse 28 about remembrance. Then the researcher details the interpretation according to Tafsir Al-Misbah, Tafsir Al-Munir, Tafsir Al-Azhar. The research methodology that the author uses is library research and uses a comparative method, namely explaining the three figures to be interpreted, then taking similarities and differences, then concluding them so that they become answers to this research.